Polarization-independent isotropic metasurface with high refractive index, low reflectance, and high transmittance in the 0.3-THz band - Sato Kento; Suzuki Takehito (Nanophotonics)
Metasurfaces substituted for naturally occurring materials make it possible to develop flat optics manipulating terahertz waves. However, the control of unprecedented material properties with metasurfaces frequently produces anisotropic material properties and has yet to be commonly adopted because of the limitation of functionalities as optical components. Here, we demonstrate an isotropic metasurface with polarization-independent material properties with the extremely high refractive index of 14.0 + j0.49, low reflectance of 1.0 %, and high transmittance of 86.9 % at 0.31 THz. Measurements by terahertz time-domain spectroscopy (THz-TDS) verify that the fabricated metasurface with a high refractive index, low reflectance, and high transmittance works for terahertz waves with any polarization direction and results in the unprecedented material characteristics with polarization independence. The relative permittivity and relative permeability are 13.9 – j1.4 and 13.8 + j2.3, respectively. The sum of the dielectric and magnetic energy losses must also be considered to verify the conservation of energy for metasurfaces. The sum of the dielectric and magnetic energy losses is very close to positive values and the conservation of energy is largely satisfied. The proposed metasurface would offer optical components with attractive functionalities such as wavefront control, directivity enhancement, and optical vortices for 6G communications.